MOOCs - Corporate Workplace Stress Management - Afzan, Ahmad Zaini; Lim, Phei Chin; Nurakmal, Abdullah@ Goh Tuo Ho; Lee, Yee Yong; Liew, Nyet Fong (2020)
The rift of workplace stress requires innovative rethinking to be addressed evocatively. Stress is a physiological response triggered by an external event that causes the individual to experience emotional, physical and cognitive symptoms. In2019, 94% of American worker’s reported sufferingstressat theirworkplace. Around 23% of them described theirstresslevels as high, while 6% said their levels ofstresswere extremely high. In Malaysia, a survey has signified thatMalaysianemployees are overworked,and sleep-deprived, with 51% travail from at least one dimension ofwork-relatedstressas well as 53% getting less than seven hours of sleep in 24 hours. For that reason, this project is aimed at establishing a Massive Open Online Courses (MOOCs)-Corporate Workplace Stress Management with the objective to succour individual or workers to reduce stress. This course is established in 6 modules; namely, (1) introduction to stress, (2) consequences of workplace stress, (3) introduction to stress management, (4) stress management in the workplace, (5) stress assessment tools, and (6) stress-free workplace. Upon completion of these modules, learners should be able to evaluate the workplace stress, practice personal and interpersonal stress management and suggestapproaches to creating a conducive working environment as part of stress reduction effort. They will be given certification to become a certified trainer to promote a life-long-learning by conducting online or face-to-face training. In the aspect of financial sustainability, value prepositions, and business model, these modules will be commercialized with minimum charges to cover the operation cost and MOOCs facilities. Notably, the modules received positive testimonials from MOOCs experts to foster deliberation of promising MOOCs-Corporate Workplace Stress Management movement and implementation.